How to Advance Social Rights without Jeopardising the Human Rights Act 1998. Issue 3 (29th April 2019) - Hunt, Paul
Abstract: When the 1948 Universal Declaration of Human Rights (UDHR) was drafted, governments grasped that human rights are needed as safeguards, not only against authoritarianism but also against the causes of authoritarianism. For this reason, the UDHR encompasses civil, political, economic, social and cultural rights. This holistic vision of human rights was obscured during the Cold War and more recently by economic neo‐liberalism. The UK government neglects social rights, which have a very low public profile, although there is evidence that the profile of these human rights is increasing. UK domestic law and practice is inconsistent with the holistic vision of human rights and the government's binding international social rights obligations. The UN Special Rapporteur on extreme poverty and human rights recommends that the UK provides for 'the legislative recognition of social rights' which can be approached in various ways. One way is to proceed social right by social right (for example, the rights to housing, health and education), and sector by sector (for example, the sectors of housing, health and education). This administrative law approach advances explicit social rights without implicating or jeopardising the Human Rights Act 1998.